Heme Signaling Impacts Global Gene Expression, Immunity and Dengue Virus Infectivity in Aedes aegypti - Bottino-Rojas, Vanessa (Public Library of Science, 2015)

(untitled) (PLoS One)
Blood-feeding mosquitoes are exposed to high levels of heme, the product of hemoglobin degradation. Heme is a pro-oxidant that influences a variety of cellular processes. We performed a global analysis of heme-regulated Aedes aegypti (yellow fever mosquito) transcriptional changes to better understand influence on mosquito physiology at the molecular level. We observed an iron- and reactive oxygen species (ROS)-independent signaling induced by heme that comprised genes related to redox metabolism. By modulating the abundance of these transcripts, heme possibly acts as a danger signaling molecule. Furthermore, heme triggered critical changes in the expression of energy metabolism and immune response genes, altering the susceptibility towards bacteria and dengue virus. These findings seem to have implications on the adaptation of mosquitoes to hematophagy and consequently on their ability to transmit diseases. Altogether, these results may also contribute to the understanding of heme cell biology in eukaryotic cells.